2009
DOI: 10.1517/13543780903183528
|View full text |Cite
|
Sign up to set email alerts
|

Cediranib: profile of a novel anti-angiogenic agent in patients with glioblastoma

Abstract: Background-Treatment strategies targeting angiogenesis have revealed promising results in pre-clinical studies and early clinical trials in patients with glioblastomas.Objective-This review evaluates the preclinical and clinical data for cediranib (AZD2171), a potent oral inhibitor of the vascular endothelial growth factor (VEGF) receptor tyrosine kinase.Methods-We summarize both pre-clinical and clinical data for cediranib with a focus on the treatment of glioblastomas.Results/conclusion-Cediranib is an effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
34
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 56 publications
2
34
0
3
Order By: Relevance
“…The critical role of VEGF/VEGFR2 in tumour angiogenesis has been demonstrated in both animal studies and clinical trials in numerous human malignancies, including glioblastoma [20][22]. PDGFRA and KIT too, may be expressed in the glioblastoma-associated vasculature, although they have been less extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…The critical role of VEGF/VEGFR2 in tumour angiogenesis has been demonstrated in both animal studies and clinical trials in numerous human malignancies, including glioblastoma [20][22]. PDGFRA and KIT too, may be expressed in the glioblastoma-associated vasculature, although they have been less extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…Bevacizumab, sorafenib, sunitinib, and pazopanib have all been approved to treat solid tumors. Cediranib (AZD2171) is an oral small-molecule inhibitor of VEGF receptor 1 (VEGFR-1), VEGFR-2, VEGFR-3, PDGFR, and c-kit that is currently in phase II testing for the treatment of tumors such as epithelial ovarian carcinoma, nonsmall cell lung cancer, glioblastoma, and colon cancer (1)(2)(3)(4). Because the primary toxicities of this drug class are on-target effects related to VSP inhibition, toxicities may be more common or severe with the newer, more potent members of this drug class currently in development.…”
mentioning
confidence: 99%
“…In some tumors in which angiogenesis is inhibited genetically or pharmacologically, cancer cells could adapt by migrating more aggressively into normal tissue [165]. Two studies describing pro-invasive adaptation, as observed by MRI, in a subset of glioblastoma multiforme patients during anti-VEGF therapy with both cedinarib and bevacizumab have confirmed this in the clinical setting [26,166].…”
Section: Resistance To Antiangiogenesis Therapymentioning
confidence: 90%